White snow, bright snow - Tresselt, Alvin R.; Duvoisin, Roger, 1900- (New York : Lothrop, Lee & Shepard Books, 1988)
When it begins to look, feel, and smell like snow, everyone prepares for a winter blizzard.
"Mulberry books"--Cover.
4.8
K-3
Caldecott 1948 Medal Winner
Keywords: Snow -- Fiction; Snow -- Fiction